Appendix A to "Analysis of Organizational factors in the practice of and the ideal for aerospace industry model-based systems engineering projects" - Shaw, Sarah G., author (Colorado State University. Libraries, 2025)
Appendix A lists the finalized tasks for each SE project that includes MBSE that was derived for this study.
Paper submitted for publication to the IEEE Open Journal of Systems Engineering, October 2025.
Keywords: model-based systems engineering (MBSE); digital engineering (DE)